2004
DOI: 10.1103/physrevlett.92.188302
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of a Product of a Surface Reaction in the Gas Phase:XeF2Reaction with Si

Abstract: Xenon difluoride interacts with Si(100)2 x 1 by atom abstraction, whereby a dangling bond abstracts a F atom from XeF2, scattering the complementary XeF. Partitioning of the reaction exothermicity produces sufficient XeF rovibrational excitation for dissociation to occur. The resulting F and Xe atoms are shown to arise from dissociation of XeF in the gas phase by demonstrating that the angle-resolved velocity distributions of F, Xe, and XeF conserve momentum, energy, and mass. This experiment documents the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This type of reactivity/surface bonding has never been demonstrated on SiNC surfaces and is known for reconstructed Si(100)(2 1) surfaces, in which an aromatic ring readily loses its aromaticity as a result of a cycloaddition to Si = Si surface dimers. [33] Approximately 20 at % fluorine was noted in quantitative XPS analysis ( Figure S6) for these XeF 2 treated particles, [30,31] suggesting the presence of SiÀF bonds on the SiNC surfaces.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…This type of reactivity/surface bonding has never been demonstrated on SiNC surfaces and is known for reconstructed Si(100)(2 1) surfaces, in which an aromatic ring readily loses its aromaticity as a result of a cycloaddition to Si = Si surface dimers. [33] Approximately 20 at % fluorine was noted in quantitative XPS analysis ( Figure S6) for these XeF 2 treated particles, [30,31] suggesting the presence of SiÀF bonds on the SiNC surfaces.…”
mentioning
confidence: 94%
“…[27] XeF 2 has long been used as an isotropic dry etchant for bulk silicon. [28,29] When it is exposed to Si surfaces at room temperature, XeF 2 produces large quantities of fluorine (FC) radicals [30,31] in close proximity to the Si surface, which cleave SiÀSi s bonds. In this context, one can imagine that FC radicals rapidly strip off surface Si atoms leaving dangling bonds, which can participate in silicon surface reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When a polyatomic molecule impinges upon a surface, it may be reflected (unreactive scattering), bind to the surface as an intact molecule (molecular adsorption), fragment into adsorbed components (dissociative adsorption), [1][2][3] or fragment into adsorbed and reflected components (abstraction). [4][5][6][7][8] The last two processes are usually exothermic; chemical bond formation between surface atoms and radicals derived from the parent molecule drives the reactions toward a lower energy state. However, a few previous studies have reported that endothermic chemisorption can occur under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…8 As a result, the surface layer consists initially primarily of SiF for most reconstructed Si͑100͒ and Si͑111͒ surfaces with possibly some SiF 2 at step edges. Once dangling bonds are passivated, the next reaction step requires breaking of Si-Si backbonds which is an activated process with a much smaller reaction probability.…”
Section: A Initial Reaction Stepsmentioning
confidence: 99%